Reduced Susceptibility to Extended-Spectrum β-Lactams in Vibrio cholerae Isolated in Bangladesh - Ceccarelli, Daniela; Alam, Munirul; Huq, Anwar; Colwell, Rita R. (Frontiers in Public Health, 2016)
β-lactams are antibiotic molecules able to inhibit cell wall biosynthesis. Among other mechanisms, resistance in Gram-negative bacteria is mostly associated with production of β-lactamase enzymes able to bind and hydrolyze the β-lactam ring. Extended-spectrum β-lactamases extend this ability also to 3rd- and 4th generation cephalosporins as well as to carbapenems and monobactams. V. cholerae is the causative agent of epidemic cholera and a public health burden for developing countries like Bangladesh. Although appropriate oral or intravenous rehydration is the therapy of choice for cholera, severe infections and V. cholerae associated septicemia are treated with antimicrobial drugs including doxycycline, erythromycin, azithromycin, ciprofloxacin and/or third-generation cephalosporins. In the years after introduction of antibiotics in clinical practice, V. cholerae developed resistance to commonly used drugs worldwide mostly through gene acquisition via horizontal gene transfer. Reduced susceptibility of V. cholerae to third-generation cephalosporins has been occasionally documented. However, carbapenemase-producing V. cholerae has been reported at higher rates than resistance to extended spectrum β-lactams, mainly associated with blaNDM-1 emergence and successful plasmid dissemination. Recent findings suggest limited β-lactam resistance is present in V. cholerae O1 isolates collected during ecological and epidemiological surveillance in Bangladesh. However a trend to intermediate-susceptibility insurgence was observed. Horizontal gene transfer of β-lactam resistance from enteric pathogens to environmental microorganisms should not be underrated, given the ability of V. cholerae to acquire new genetic information.